Measuring agricultural trade integration in Southeast Asia - Bouët, Antoine; Elbehri, Aziz; Nguyen, Duc Bao; Traoré, Fousseini (Center for Economic Integration, 2022)
This paper offers an evaluation of agricultural trade integration in Southeast Asia. Since the ultimate objective is to provide policy recommendations, the indicators presented include those obtained from a measurement based on trade barriers: tariffs applied on imports, tariffs faced by exports, customs procedures and trade facilitation measures, and nontariff measures. A new estimation of the trade impact of nontariff measures in the agrifood sector is provided, based on refinements to the methodology of Kee, Nicita, and Olarreaga (2009) and Ghodsi, Grübler, and Stehrer (2016a). Globally, the Southeast Asian region appears to be relatively open to the world, but regional integration could be strengthened, particularly in the agriculture and food sectors. Specifically, a convergence of Sanitary and Phytosanitary measures and Technical Barriers to Trade measures could achieve more integration.